Gastrointestinal pathologists' perspective on managing risk in the distal esophagus: convergence on a pragmatic approach. Issue 1 (11th May 2018) - Bellizzi, Andrew M.; Hafezi‐Bakhtiari, Sara; Westerhoff, Maria; Marginean, E. Celia; Riddell, Robert H.
Abstract: Here, we discuss recent updates and a continuing controversy in the diagnosis and management of Barrett's esophagus, specifically the recommendation that the irregular Z‐line not be biopsied, the diminished status of ultrashort‐segment Barrett's esophagus, the evidence basis for excluding and including the requirement of goblet cells for the diagnosis of Barrett's esophagus, and the conclusion that histologically confirmed low‐grade dysplasia is best managed with endoscopic ablation rather than surveillance. We reference the American Gastroenterological Association and College of Gastroenterology and the British Society of Gastroenterology guidelines throughout, with the thesis that the field is converging on the concept of applying scarce medical resources to the diagnosis, surveillance, and therapy of patients most likely to derive benefit.